Implementation of education for sustainability in the Elementary School: a review (Research, Society and Development, 2020)
Scarce approach to sustainability in basic education will have a significant impact on the prosperous and sustainable future of humanity. Therefore, the aim of this study is to analyze research articles on the implementation of education for sustainability (EfS) in elementary education, published after the approval of 2030 until March 2020. For that, systematic searches were carried out in the SciELO, Google Scholar and ERIC databases, using exclusion processes in several stages, which ended in 10 revised articles. The results pointed to the existence of gaps in the literature on the ways in which EfS has been approached in the context of the elementary school classroom, despite its importance in the current unsustainable situation on the planet. The analyzed articles consider EfS important, because it contributes to change knowledge, values and attitudes towards a sustainable future; moreover, they show difficulties in implementing EfS in everyday educational practices, due to the complexity of implementation, in addition to resistance by some teachers to innovate in educational practice. Therefore, this review can be useful, for informing the current educational approaches related to the implementation of sustainability in elementary education, as well as for proposing innovative practices of EfS at this level of education.